Model-aided atpE gene knockout strategy in Escherichia coli for enhanced succinic acid production from glycerol - Mienda, B. S. (Taylor and Francis Ltd., 2016)
Succinic acid is an important platform chemical with a variety of applications. Model-guided metabolic engineering strategies in Escherichia coli for strain improvement to increase succinic acid production using glucose and glycerol remain largely unexplored. Herein, we report what are, to our knowledge, the first metabolic knockout of the atpE gene to have increased succinic acid production using both glucose and alternative glycerol carbon sources in E. coli. Guided by a genome-scale metabolic model, we engineered the E. coli host to enhance anaerobic production of succinic acid by deleting the atpE gene, thereby generating additional reducing equivalents by blocking H+ conduction across the mutant cell membrane. This strategy produced 1.58 and.49 g l−1 of succinic acid from glycerol and glucose substrate, respectively. This work further elucidates a model-guided and/or system-based metabolic engineering, involving only a single-gene deletion strategy for enhanced succinic acid production in E. coli.